The Effectiveness of the Al-Fatih Method in Improving the Quality of Reading the Quran in Islamic Boarding Schools - A. Faizul Mubarak; Febri Habibi Ilham (Journal of Islamic Education Research, 2024)
This study seeks to evaluate the efficacy of the Al-Fatih approach in enhancing the proficiency of students in Islamic boarding schools in reading the yellow book. The research methodology employed is qualitative and focuses on providing a descriptive analysis of the occurrences seen at the research site. Data collection was conducted using interviews, observations, and documentation. Certain kids struggle with comprehending and perusing the yellow book. The data analysis results indicate that the Al-Fatih method's efficacy in enhancing students' reading proficiency of the Yellow Book at the Nurul Jadid Islamic Boarding School is achieved through the implementation of the Training of Trainers (ToT) process and the Level and Tiered approach. The Al-Fatih method significantly contributes to the advancement of curricula in Islamic boarding schools and offers valuable insights into the use of novel approaches in religious settings. In addition, this approach also offers valuable understanding of the overall potential for enhancing academic learning in Islamic boarding schools.